A description of the SENA robotic wheelchair - Gonzalez, J.; Muaeoz, A.J.; Galindo, C.; Fernandez-Madrigal, J.A.; Blanco, J.L. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
This paper describes a robotic wheelchair called SENA. It is based on a commercial powered wheelchair which has been endowed with several sensors and devices managed by an onboard laptop. The sensorial system of SENA entails a proximity laser scanner, a ring of infrared sensors, a camera mounted on a pan&tilt unit, and two rotating sonars. SENA is a long-term project aimed to cover the requirements needed to perform in daily indoor environments. Some experiences of the use of our robotic wheelchair are also described at the end of the paper